The impact of banks and non-bank financial institutions on local economic growth in China - Xiaogiang Cheng; Hans Degryse (Bank of Finland, Institute for Economies in Transition (BOFIT), 2007)
This paper provides evidence on the relationship between finance and high growth in China. Employing data for 27 Chinese provinces over the period 1995-2003, we assess the impact of banks and non-bank financial institutions on local economic growth. We argue that banks have had a larger impact than non-banks on local economic growth as they benefited earlier and more profoundly from China's financial reforms than their non-bank counterparts.
URN:NBN:fi:bof-201408072074
Keywords: E44; G21; 330; growth; financial development; Chinese provinces; banks